2017
DOI: 10.1080/14043858.2017.1387451
|View full text |Cite
|
Sign up to set email alerts
|

Punishment justifications in rape cases: a community study

Abstract: Norway is one of the countries with the most progressive criminal justice systems in the Western world. Traditionally, the Norwegian criminal justice system has been mainly based on treatment and deterrence perspectives. While it is believed that criminal justice practices should be in accordance with public attitudes, few studies in Scandinavia have investigated public attitudes towards criminal justice sanctions in a methodologically sound manner. The current study is the first to investigate the attitudes o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 46 publications
(93 reference statements)
0
4
0
Order By: Relevance
“…Attitudes toward sexual offenders are generally quite negative (Klein, 2015; Willis et al, 2013); however, there are some demographic differences that consistently affect how perceivers feel about offenders. The largest difference in the literature is by gender, with more negative beliefs about offenders held by females than males (Bergstrøm et al, 2017; Willis et al, 2013). Specifically, females show significantly higher levels of fear toward offenders than do males (Kernsmith et al, 2009; Koon-Magnin, 2015).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Attitudes toward sexual offenders are generally quite negative (Klein, 2015; Willis et al, 2013); however, there are some demographic differences that consistently affect how perceivers feel about offenders. The largest difference in the literature is by gender, with more negative beliefs about offenders held by females than males (Bergstrøm et al, 2017; Willis et al, 2013). Specifically, females show significantly higher levels of fear toward offenders than do males (Kernsmith et al, 2009; Koon-Magnin, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Parental status can also have an effect on offender attitudes, with parents being more likely to believe offenders cannot change and that they are dangerous (Klein, 2015). Many studies show that less formal education is also positively correlated with negative attitudes about offenders (King & Roberts, 2015; Shackley et al, 2014; Socia & Harris, 2016; Willis et al, 2013), although one study found that individuals with higher levels of education responded more negatively to offenders (Bergstrøm et al, 2017). Another study looked at how the Big Five personality characteristics (McCrae & Costa, 1999) predicted attitudes toward offenders and found that those high in openness to experience or agreeableness were significantly more likely to believe in rehabilitation, with those high in extroversion having more negative attitudes about offenders (Olver & Barlow, 2010).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations